Current trends in bee conservation and habitat restoration in different types of anthropogenic habitats - Kline, Olivia; Joshi, Neelendra K. (Frontiers in Ecology and Evolution, 2024)
Recent declines in bee populations and ranges have been cause for concern due to the valuable pollination service that they provide. Several factors have been proposed to contribute to these declines, including habitat loss, pathogen spread, and pesticide usage, so many pollinator conservation schemes have involved the addition of pollinator-friendly habitat through wildflower plantings and artificial nesting sites. Because of this, many efforts have been made to enhance bee populations across different landscape types, including natural, agricultural, urban, and industrial areas. Many of these schemes have focused on providing habitat for bees and other animal pollinators in agricultural landscapes, but other managed areas, such as cities, suburbs, and industrialized areas may have untapped potential for pollinator conservation. Available green space can be enhanced to provide healthy forage and safe nesting sites for pollinators. As these areas are also often frequented by human residents, the needs and perceptions of people, as well as the potential benefits for pollinators, must be considered to ensure the success of pollinator conservation on anthropogenic habitats.